2014
DOI: 10.1515/ejnm-2014-0042
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoliposomes: opportunities and challenges

Abstract: Combining liposomes with magnetic nanoparticles is an intriguing approach to create multifunctional vesicles for medical applications, which range from controlled drug delivery vehicles to diagnostic imaging enhancers. Over the past decade, significant effort has been invested in developing such hybrids -widely known as magnetoliposomes -and has led to numerous new concepts. This review provides an overview on of the current state of the art in this field. The concept of magnetic fluid hyperthermia and stimuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 34 publications
0
38
0
2
Order By: Relevance
“…MLs were formed by 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) embedded with two types of NPs: citrate-coated Fe 3 O 4 NPs and oleic acid-coated g-Fe 2 O 3 NPs. A consistent number of reports (recently summarized in a comprehensive review 34 ) have demonstrated that the citrate coating allows for the encapsulation of magnetic NPs within the liposome lumen, while the oleic acid coating takes to their embedding at the level of the lipid bilayer. MLs were dispersed in bovine serum at different protein concentrations (10% and 55% v/v related to in vitro and in vivo protein concentrations in the biological environment) and the release was evaluated after exposure to a 5.7 kHz alternating magnetic field.…”
Section: Cobalt Ferrite (Cofe 2 O 4 )mentioning
confidence: 92%
“…MLs were formed by 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) embedded with two types of NPs: citrate-coated Fe 3 O 4 NPs and oleic acid-coated g-Fe 2 O 3 NPs. A consistent number of reports (recently summarized in a comprehensive review 34 ) have demonstrated that the citrate coating allows for the encapsulation of magnetic NPs within the liposome lumen, while the oleic acid coating takes to their embedding at the level of the lipid bilayer. MLs were dispersed in bovine serum at different protein concentrations (10% and 55% v/v related to in vitro and in vivo protein concentrations in the biological environment) and the release was evaluated after exposure to a 5.7 kHz alternating magnetic field.…”
Section: Cobalt Ferrite (Cofe 2 O 4 )mentioning
confidence: 92%
“…showed that the monoolein cubic phase with MNPs subjected to AMF for 10 minutes indicate Pn3m to HII phase transition. [40] Other works [28,30,32,41,42] rely on the so-called magnetothermal effect observed in an alternating magnetic field. This effect reveals itself as temperature rises, transferring heat to the immediate vicinity when the magnetic nanoparticles are exposed to the alternating magnetic field of sufficiently high frequency (typically from several kHz to hundreds of kHz) due to the Néel and Brownian relaxation [43].…”
Section: Low-frequency Alternatingmentioning
confidence: 99%
“…[24] Magnetic nanoparticles and ions are currently of great interest in research related to medical applications [25] and are used as contrast agents for theranostics in medical imaging applications [26]. Few reported studies examined the effect of the addition of nanoparticles to liquid crystalline hexagonal phase [27], liposomes [28,29] and cubosomes [30][31][32] creating a magnetic responsive system.…”
Section: Introductionmentioning
confidence: 99%
“…However, mesoporous silica materials are gradually receiving interest due to their unique properties, such as well-established drug delivery properties (Vallet-Regi et al, 2007) and versatility for creating high-performing hybrid materials. Besides mesoporous silica, other multifunctional devices based on various nano-platforms were discovered (Soenen et al, 2011;Monnier et al, 2014;Chauhan et al, 2018;Hameed et al, 2018).…”
Section: Introductionmentioning
confidence: 99%